Inclusive Education in A Hybrid Setup for Early Childhood Education - Hajah Mahanom Binti Haji Basri (Universitas Serambi Mekkah, 2024)
Inclusive education in a hybrid setup for Early Childhood Education in Malaysia represents a pivotal shift in the country's approach to ensuring equal educational opportunities for all children. This innovative approach merges the principles of inclusivity to create a more accessible and flexible learning environment. Little Leaders Childcare Centre is the first Inclusive registered nursery in Selangor state. We Believe in educating children through an inclusive diversity way, full of love, compassion and understanding for each other from an early age forming a holistic development. Little Leaders Childcare Centre (LLCC) is the first hybrid childcare center in Malaysia. To open a childcare center in Malaysia, you are required to get licenses from Local Authority, Health Ministry and Fire Department. LLCC has all these three licenses. LLCC objectives are assisting parents working in Menteri Besar Selangor incorporated, government and private departments located in Bangunan Darul Ehsan and its surroundings. Helping special children so that they can be given early intervention through regular therapy sessions. Provide children the opportunity and space to enjoy complete facilities in a conducive environment. Being a ‘world class’ model is a world-class example of a hybrid center. Vision: maximizing every child’s potential through structured, fun-filled activities. Mission: to instill good values based ON Islamic teachings; to develop strong character, confidence and self-esteem; and to nurture caring, responsible and outstanding leaders for our society, at par with global standards. Objective: the concept of inclusive education centers on providing children with disabilities or special needs opportunity to learn alongside their typically developing peers.